2004
DOI: 10.1007/s00420-004-0548-8
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer among pesticide applicators: a meta-analysis

Abstract: The increased meta-rate ratio for prostate cancer in agricultural pesticide applications provides additional evidence for a possible relationship between pesticide exposure and prostate cancer. The homogeneity observed between the individual rate ratios, after we had regrouped the data according to geographic location, tends to increase the consistency of the association. However, the data available from the individual studies do not provide sufficient exposure information for firm conclusions to be drawn abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 72 publications
6
48
1
6
Order By: Relevance
“…Results from meta-analyses based on these studies are consistent with a weak, positive association between farming and prostate cancer. 100 More recent epidemiologic evidence from a number of different studies now, more convincingly, shows that prostate cancer is related to pesticide use specifically. In one of the largest prospective studies of pesticide exposures published to date, the Agricultural Health Study (AHS), which was conducted in Iowa and North Carolina, a small but significant excess prostate cancer risk was CA CANCER J CLIN 2013;63:120-142 VOLUME 63 _ NUMBER 2 _ MARCH/APRIL 2013 observed among both farmers (19% excess) and commercial pesticide applicators (28% excess).…”
Section: Prostate Cancermentioning
confidence: 99%
“…Results from meta-analyses based on these studies are consistent with a weak, positive association between farming and prostate cancer. 100 More recent epidemiologic evidence from a number of different studies now, more convincingly, shows that prostate cancer is related to pesticide use specifically. In one of the largest prospective studies of pesticide exposures published to date, the Agricultural Health Study (AHS), which was conducted in Iowa and North Carolina, a small but significant excess prostate cancer risk was CA CANCER J CLIN 2013;63:120-142 VOLUME 63 _ NUMBER 2 _ MARCH/APRIL 2013 observed among both farmers (19% excess) and commercial pesticide applicators (28% excess).…”
Section: Prostate Cancermentioning
confidence: 99%
“…More recent systematic review studies or case-control studies reported positive association between exposure to pesticides and several cancers including prostate cancer (Van Maele-Fabry and Willems, 2004;Koutros et al, 2010;Doolan G et al, 2014), non-Hodgkin lymphoma (NHL) (Merhi et al, 2007;Balasubramaniam et al, 2013;Yildirim et al, 2013;Schinasi and Leon, 2014), leukemia (Merhi et al, 2007;Van Maele-Fabry et al, 2008), multiple myeloma (Merhi et al, 2007) and lung cancer (Ganesh et al, 2011;Luqman et al, 2014). In the case of esophageal or gastric cancer, no relationship with pesticide usage was reported in recent Turkey study (Yildirim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There have been a lot of studies to evaluate the association between occupational exposure to pesticide and cancer risk. More recent systematic review studies or case-control studies reported positive association between exposure to pesticides and several cancers including prostate cancer [10][11][12], non-Hodgkin lymphoma (NHL) [13][14][15][16], leukemia [13,17], multiple myeloma [13] and lung cancer [18,19]. Alavanja et al integrated the epidemiological, molecular biology, and toxicological evidence emerging from recent literature assessing the link between specific pesticides and several cancers including prostate cancer, non-Hodgkin lymphoma (NHL), leukemia, multiple myeloma, and breast cancer [20].…”
Section: Commentarymentioning
confidence: 99%